ChatGPT in Sustainable Business, Economics, and Entrepreneurial World: Perceived Usefulness, Drawbacks, and Future Research Agenda - Rahaman, Md. Saidur; Ahsan, M. M. Tahmid; Anjum, Nishath; Dana, Leo Paul; Salamzadeh, Aidin; Sarker, Dhruba; Rahman, Md. Mizanur (Journal of Entrepreneurship, Business and Economics, 2024)
Considering some drawbacks, the application of Chat Generative Pre-training Transformer (ChatGPT) in sustainable business, economics, and entrepreneurial projects has numerous advantages. This review seeks to comprehend the present scenario of ChatGPT utilization in business, economics, and entrepreneurial domains and its perceived benefits and drawbacks. The researchers employed a scoping literature review. Researchers used the SCOPUS and Google Scholar databases from January 2023 to March 2024. The research employed a five-stage process to design the study along with the guidelines of the PRISMA-ScR checklist. Finally, to synthesize the result, researchers used a thematic framework. Researchers included 40 studies excluding non-English records, clinical studies on ChatGPT, comparisons of ChatGPT performance on examinations to people and publications from non-academic sources like newspapers, internet websites, magazines, etc. The findings reveal that ChatGPT can augment decision-making procedures and boost the effectiveness of diverse business, economic, and entrepreneurial operations. In addition, organizations can enhance their ability to engage with consumers and clients, resulting in improved relationship-building and quick decision-making processes. Moreover, the overdependence on ChatGPT raises ethical and privacy apprehensions. It is crucial to consider that ChatGPT requires further improvement in terms of reliability; it is currently prone to numerous errors and generates unsuitable responses for some contexts. The study also provides directions for future research on the application of ChatGPT. Ultimately, business organizations, entrepreneurs, and general readers will comprehensively understand the advantages and disadvantages of incorporating ChatGPT in the business, economics, and entrepreneurship world. Research Paper Keywords: ChatGPT; Challenges; Economics; Entrepreneurship; Sustainable Business; Perceived Usefulness; Scoping Review; and TAM Reference to this paper should be made as follows: Rahaman, M.S., Ahsan M.M.T, Anjum, N., Dana, L.P., Salamzadeh, A., Sarker D., &Rahman, M.M. (2024). ChatGPT in Sustainable Business, Economics, and Entrepreneurial World: Perceived Usefulness, Drawbacks, and Future Research Agenda. Journal of Entrepreneurship, Business and Economics , 12 (1), 88–123.